Reproductive and larval cycle of the scallop Argopecten purpuratus (Ostreoida: Pectinidae), during El Niño-La Niña events and normal weather conditions in Antofagasta, Chile - Avendaño, Miguel (2008)
Seasonality, amplitude, and magnitude of spawning events were determined for Argopecten purpuratus in the La Rinconada marine reserve, Antofagasta, Chile, between December 1995 and January 2004. During the same period, samples of scallop larvae were obtained in vertical plankton hauls recovered within this reserve in an area routinely exposed to circular, gyre-like currents which helped retain the larvae within the bay. The reproduction of this population in normal or cool (e.g. "La Niña", 1998-2000) years occurred throughout the year, with a more active period between September and April, declining in June and August; this contrasted with the warmer "El Niño" oceanographic period of 1997-98 in which reproductive activity was more intense and prolonged throughout the entire year. The reproductive events in this population were mostly synchronous, although one asynchronous period occurred each year following the more intense March to May spawnings. This reproductive activity generated a continuous presence of larvae in the area in which no strict relation could be found between the intensities of spawning and numbers of larvae in the water. Larval presence was, however, generally correlated with active spawning periods. Important increases in larval numbers recorded at the end of 1999 and the beginning of 2003 were correlated with census data showing a higher percentage presence of broodstock over 90 mm in shell length during these years. An adequate stock of this size class is needed for a successful seed capture program in the reserve (for mass culture).